2020
DOI: 10.1016/j.bbmt.2019.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Relapse Prevention with Tyrosine Kinase Inhibitors after Allogeneic Transplantation for Philadelphia Chromosome–Positive Acute Lymphoblast Leukemia: A Systematic Review

Abstract: Relapse after stem cell transplantation for Philadelphia chromosomeÀpositive (Ph+) acute lymphoblastic leukemia (ALL) remains a significant challenge. In this systematic review, we compare survival outcomes of second-generation tyrosine kinase inhibitors (TKIs) nilotinib and dasatinib with first-generation TKI imatinib when these agents are used after allogeneic hematopoietic stem cell transplantation (allo-HSCT) in Ph+ ALL. In addition, we review the literature on TKI use to prevent relapse in patients who pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…7 Systematic review by Warraich et al comprising 18 prospective and retrospective studies with 462 participates showed that utilisation of TKI (all generations) post allo-HSCT for adults patients in CR1 improved OS when given as prophylactic or pre-emptive regimen. 27 However, it is unclear whether this observed improvement of TKIs is significant in children. To our knowledge, our research is the first systematic review to investigate whether adding TKIs to conventional chemotherapy is indeed beneficial in paediatric Ph+ALL.…”
Section: Discussionmentioning
confidence: 99%
“…7 Systematic review by Warraich et al comprising 18 prospective and retrospective studies with 462 participates showed that utilisation of TKI (all generations) post allo-HSCT for adults patients in CR1 improved OS when given as prophylactic or pre-emptive regimen. 27 However, it is unclear whether this observed improvement of TKIs is significant in children. To our knowledge, our research is the first systematic review to investigate whether adding TKIs to conventional chemotherapy is indeed beneficial in paediatric Ph+ALL.…”
Section: Discussionmentioning
confidence: 99%
“…TKIs-based maintenance post-HSCT can reduce relapse risk and should be considered a valuable option ( 56 ). Future studies addressing the same issue in a pediatric population are needed, although some clinical experiences support the positive role of the drug in this clinical setting ( 57 ).…”
Section: Consensus Papermentioning
confidence: 99%
“…Efficacy of RUX in GVHD is attributed to the immunosuppressive properties of the drug and the inhibition of a wide number of cytokines involved in GVHD. However, the application of RUX in MF cannot be compared to the use of BCR-ABL-specific tyrosine kinase inhibitors (TKIs), such as imatinib, in patients transplanted for CML or Ph+ acute lymphoblastic leukemia (ALL) [ 128 , 129 ]. The efficacy of TKIs in CML and Ph+ ALL is attributed to a direct inhibition of the aberrant fusion protein, and a molecular response to the treatment is generally observed, whereas RUX is only acting on enhanced signal transduction without a significant decrease of the malignant clone [ 116 ], at least in most patients.…”
Section: Therapeutic Approaches To Reduce Inflammation and To Prevmentioning
confidence: 99%